Ecological conditions for spread of the invasive snail Physa marmorata (Pulmonata: Physidae) in the Ivory Coast - (:unkn) unknown (My University, 2008)
Physa marmorata, originally described from the Lesser Antilles, was introduced into Africa before 1900 and has previously been reported from Bénin, Togo, Ghana, Nigeria and South Africa. Here we show that it is also common in temporary ponds, fish ponds, dams and streams in the La Mé and Agnéby basins, southern Ivory Coast. Population dynamics were studied in one river in Agboville and in one permanent pond in Attinguié. Fortnightly sampling carried out throughout 2005 at the two sites revealed two main periods of recruitment: during the first rainy season in July and during the second rainy season in October. In the Agboville river, a positive association was found between P. marmorata densities and percentage cover of the aquatic plants Ipomea aquatica and Pistia stratiotes. Similar associations were found between P. marmorata densities and both high water redox potential and rainfall values. However in the Attinguié pond, a negative association was observed between Melanoides tuberculata and P. marmorata densities. We discuss the timing, status and potential consequences of the invasion of this snail species into the Ivory Coast and the African continent.
Keywords: African Research